IMPLEMENTASI MERDEKA BELAJAR KAMPUS MERDEKA UNTUK MAHASISWA - Maharani, Shinta Ikrana; Zaenul Fitri, Agus; Aziz, Abd. (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
Merdeka Learning Merdeka Campus (MBKM) is a higher education concept that aims to give students freedom to organize and take control of their learning process. This concept shifts the traditional paradigm of higher education as a reward for lecturers towards a more open and mindful approach to students. MBKM includes giving freedom to students in choosing courses, determining learning methods, and recognizing learning outside the campus. The research used in this journal is library research or library research, with data and information collection techniques through reading literature or written sources such as books, previous research, papers, journals, articles, reports and magazines. In its implementation, MBKM focuses on students, but in line with its goals and focus, there are challenges in implementing MBKM in tertiary institutions.